Participación familiar en la educación - Tobar Rueda, Mayra Alexandra (2015)
Education today is no direct competition for teachers, as one of the main members are parents and do not meet fully their fundamental role in the education of their children because they do not care about the daily reinforcement house on the knowledge acquired in the school. Has conducted several studies on this subject, which shown that students who have poor relationships with their parents and the school, have low academic performance, otherwise with those who have a good relationship between parents and entity education-students, It talks about the importance of good relationship between the family and the school and therefore must be a shared task. For the efficient conduct of this investigation is used the No Experimental Method and Transactional Method, since field data will be collected through direct surveys with the community involved. Therefore research will provide a lot help and will directly benefit the entire education community, enabling them to improve their academic performance inside and outside the classroom in a strategic and appropriate manner, considering the active participation of all, in order to prevent and not to regret failures school, for which it carries out a reflection on the family as a basic institution and the most important. Is believed that education is so significant as to delegate only to teachers, so parents should be active participants in the educational process of their children.